Vulnerabilidade as Inundações, Abordagens Metodológicas de Avaliação e Ações para a Resiliência - Chicombo, Tomé Francisco (2024)
This article proposes a reflection on vulnerability to floods, its compounds, methodological approaches, analysis scales and most important measures to build resilience. It was constructed by means of bibliographical revision of available literature. It was found that four main approaches are used when it comes to assessing vulnerability to floods, namely: vulnerability curves, damage matrices, vulnerability indicators and the modeling-based approach. Those approaches adopt diferente analysis scales, from micro to national, from local to regional ones. Resilience construction measures must consider different factors, specially: physical-environmental, social, economic, social behavioral and political administrative, all of them taken together. The conclusion is that assessment approaches to floods must always be based on the context in which they occur, analyzing vulnerability as an intrinsic characteristic of a system or element. On the other hand, the adoption of adaptation strategies must be carried out in a holistic and integrated way, paying attention to the way in which each factor contributes particularly to increasing vulnerability in communities.